Implementation of STEP Application Protocol 224 in an automated manufacturing planning system. - Sharma, R.; Gao, James X. (Professional Engineering Publishing, 2002)
This paper reports the results of an on-going research project at Cranfield University in collaboration with a leading consultant company. A major objective of the research to develop a new generation process planning system using the latest tools and technologies, and to fully comply with the international standard for the exchange of product model data (STEP) Application Protocol 224 (AP224) for process planning using machining features. Although AP224 has been accepted as an international standard, there is a surprising lack of compatible software packages in the market. The developed prototype STEP-enabled manufacturing planning system (SMPS) can generate process plans and associated documents from AP224 files automatically, without any user interaction. The system consists of decision logic stored in an external database that makes it generic and compatible with any manufacturing application. A graphical tool is provided for knowledge/logic capture. The system can also accept a feature tree generated using the feature model editor (FME), which has been developed as an add-on to the system. The FME is intended to be a tool for conceptual design of simple components. The FME feature tree is used in the early design stage while the AP224 file generated from the detailed design model is used in the later stages. The prototype system is intended for single-piece machined (prismatic) parts and has been tested with case studies provided by the project collaborators.